2002
DOI: 10.1034/j.1600-0536.2002.460101.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis: the cellular effectors

Abstract: Contact hypersensitivity reactions are mediated by lymphocytic effector cells. Until recently it was believed that the most important of these were CD4 π T lymphocytes. However, there is growing evidence that in many instances the predominant effector cell may be a CD8 π T lymphocyte, with in some instances CD4 π cells performing a counter-regulatory function. Here we review the roles of CD4 π T helper (Th) cells and CD8 π T cytotoxic (Tc) cells, and their main functional subpopulations (respectively, Th1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(88 citation statements)
references
References 41 publications
1
84
1
2
Order By: Relevance
“…HLArestricted Ni-reactive T cell lines and clones of both CD4 and CD8 phenotypes have repeatedly been isolated by NiSO 4 or NiCl 2 stimulation of T cells from peripheral blood or skin lesions of allergic patients and even from nonsensitized individuals (1,9,44,45). Recent data imply that Ni 2ϩ mediate TCR/MHC contact by formation of complexes involving amino acids of TCR and/or MHC as coordination partners (24,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…HLArestricted Ni-reactive T cell lines and clones of both CD4 and CD8 phenotypes have repeatedly been isolated by NiSO 4 or NiCl 2 stimulation of T cells from peripheral blood or skin lesions of allergic patients and even from nonsensitized individuals (1,9,44,45). Recent data imply that Ni 2ϩ mediate TCR/MHC contact by formation of complexes involving amino acids of TCR and/or MHC as coordination partners (24,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations in mice found CHS to be associated with CD4 ϩ T lymphocyte function and to be compromised when such cells were deleted (15,16). However, there is growing evidence that in many instances the predominant effector cell in CHS may be a CD8 ϩ T lymphocyte (13,17,18). Wang et al (17) clearly demonstrated that the deletion of CD8 ϩ Tc1 cells had a more significant suppressive effect than the deletion of CD4 ϩ Th1 cells in CHS responses to 2,4-dinitrofluorobenzene (DNFB).…”
Section: T-bet Is Known As a Th1 Lineage Commitment Transcription Facmentioning
confidence: 99%
“…Contact dermatitis and CHS are delayed-type hypersensitivity reactions that are mediated by haptenspecific T cells (12). Skin sensitization resulting in contact dermatitis and CHS is dependent on the initiation of specific T lymphocyte responses (11,13). Until recently it was believed that the most important cells in these responses were CD4 ϩ T lymphocytes.…”
Section: T-bet Is Known As a Th1 Lineage Commitment Transcription Facmentioning
confidence: 99%
“…21 The primary effector cell in DHT is CD4 TL while the main effector cell in ACD is CD8 TL, which has its action supported by type 1 auxiliary TL and suppressed by other CD4 T cells. 47,88 A series of findings, described below, led to these conclusions.…”
Section: Lymphocytes Effector Lymphocytesmentioning
confidence: 97%